Profitability of State-Owned Commercial Banks in Bangladesh Based on Islamic PLS and Conventional Interests - Ahmad, Faisal (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: This research compares the profitability of state-owned commercial banks in Bangladesh operating under Islamic Profit-Loss Sharing (PLS) principles with conventional interest-based systems. Design/Method/Approach: This study uses a comparative quantitative approach, analyzing 10 years of financial data from state-owned commercial banks in Bangladesh. Profitability indicators (ROA, ROE, NPM, EPS) are compared between Islamic PLS and conventional interest-based operations. Statistical tools like t-tests and panel regression are used to identify significant differences and impacts. Findings: The study finds that state-owned commercial banks in Bangladesh operating under Islamic PLS models generally exhibit more stable but modest profitability than their conventional interest-based counterparts. While Return on Assets (ROA) and Net Profit Margin (NPM) are slightly higher in traditional operations, Islamic banking shows lower volatility and better risk-sharing attributes. The panel regression analysis reveals that the banking model significantly influences profitability, with conventional interest-based systems yielding higher short-term returns, whereas Islamic PLS promotes financial resilience. Originality/Values: This study uniquely compares profitability between Islamic PLS and conventional interest systems within state-owned banks in Bangladesh. It offers policymakers and bank managers valuable insights on optimizing dual banking operations.